Implementasi Sistem Informasi Warga Berbasis Web Menggunakan Opensid Di Desa Kangkung, Kecamatan Mranggen, Kabupaten Demak - Arkhan Subari; Heru Winarno; Saiful Manan (Jurnal Pengabdian Vokasi, 2021)
Kangkung Village is one of the villages in Mranggen District, Demak Regency, which is one of the villages directly adjacent to Semarang, in the east. Because it is on the border with Semarang, Kangkung village is a village with a dense population. It is located in a busy main route area and is in the middle of an industrial area. The total population in Kangkung Village is approximately 1,400 families. The average education level of the people of Kangkung Village is high school and college. Kangkung Village is located in the border area between Semarang and Demak Regency, so it is a relatively developed area but population administration information and file services have not been provided fully effectively, therefore it requires a population data information system that is quite easy to access, fast, accurate and up to date. With these conditions, this service is carried out to help the people of Kangkung Village, Mranggen District, Demak Regency in terms of population information system applications which include population information based on age, sex, occupation and information on former population administration including family card information and also ID cards that are accurate, fast and up to date. Thus users of this information can be immediately served when data requests from residents of Kangkung Village, Mranggen District, Demak District. The service is carried out through the following stages: licensing the implementation of activities to related parties, collecting related data, designing and creating an information system application for residents of Kangkung Village, Mranggen District, Demak District based on the data obtained, testing the application to find out whether the application according to need. The result of this activity is that there is a web-based citizen information system that can present population data that is often needed quickly, accurately and up to date. With this information system, population data can be presented faster than the manual method.